A Structure-Based Computational Vaccine Strategy for the Emerging Isfahan Virus: In-Silico Vaccine Designing - Ahmad, Sajjad; Amin, Sidra; Rahiyab, Muhammad; Rooh-Ullah; Iqbal, Arshad; Ali, Syed Shujait; Ali, Liaqat; Khan, Salman; Khan, Hyat; Hussain, Zahid (International Health Review, 2025)
Isfahan virus (ISFV) is a recently discovered zoonotic disorder that causes painful and severe neurological effects in humans. The virus was initially identified after an epidemic in horses and cattle in 1916, and was later isolated from cattle in Richmond, Indiana in 1925. Currently, no effective vaccine is available for ISFV virus. Therefore, the current work aimed to generate a multi-epitope-based vaccine (MEV) candidate targeting Isfahan virus glycoprotein and large polymerase protein. From these proteins, nine epitopes (three T-cell and B-cell epitopes) were finally designated based on their non-allergenic, non-toxic, and antigenic properties. The selected epitopes, together by suitable adjuvant, enabled the development of an antigenic ISFV-MEV candidate free from allergic reactions. Computational modeling showed that the designed MEV binding strongly interacted with human TLR-3 receptors. Furthermore, immune simulations research established that the ISFV-MEV candidate has the potential to elicit robust immune system reactions in humans. Overall, the outcomes of these in silico studies are promising; however, a subsequent in vivo validation is recommended to confirm its potential as a future vaccine candidate.